2008
DOI: 10.1158/1535-7163.mct-08-0826
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a nonkinase target mediating cytotoxicity of novel kinase inhibitors

Abstract: In developing inhibitors of the LIM kinases, the initial lead molecules combined potent target inhibition with potent cytotoxic activity. However, as subsequent compounds were evaluated, the cytotoxic activity separated from inhibition of LIM kinases. A rapid determination of the cytotoxic mechanism and its molecular target was enabled by integrating data from two robust core technologies. Highcontent assays and gene expression profiling both indicated an effect on microtubule stability. Although the cytotoxic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
130
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(136 citation statements)
references
References 35 publications
(43 reference statements)
5
130
0
1
Order By: Relevance
“…In another experiment, we tested whether (N-[5-[2,6-dichloro-phenyl]-5-difluoromethyl-2H-pyrazol-3-yl]thiazol-2-yl)-isobutyramide, a recently described LIMK inhibitor (33,34), also called LIMKi (Fig. 6A), was able to stabilize microtubules.…”
Section: Limk Inhibition Causes Microtubule Stabilizationmentioning
confidence: 99%
“…In another experiment, we tested whether (N-[5-[2,6-dichloro-phenyl]-5-difluoromethyl-2H-pyrazol-3-yl]thiazol-2-yl)-isobutyramide, a recently described LIMK inhibitor (33,34), also called LIMKi (Fig. 6A), was able to stabilize microtubules.…”
Section: Limk Inhibition Causes Microtubule Stabilizationmentioning
confidence: 99%
“…Bristol Myers Squibb reported that substituted pyrazoles with an aryl di-ortho chloro group were potent LIMK inhibitors. 13 Similarly we found that pyridines substituted with aryl rings adjacent to the thiazole ring provided substantial improvements in potency as in 3a which had a LIMK1 potency of 15 nM. Even more importantly compound 3a was active in the p-cofilin cellular assay with an IC50=3 µM.…”
mentioning
confidence: 54%
“…Given that LIMK inhibitors have now been developed by a number of drug discovery efforts (20)(21)(22)(23)(24), it should be possible for thorough pharmacological proof of concept experiments to be undertaken to test the hypothesis that LIM kinases are valid cancer targets. Although the use of LIMK inhibitors to block cancer cell invasiveness and metastasis was one initial potential application (12), several recent reports indicate that they may be useful for treating primary tumors (21,25).…”
Section: Future Directionsmentioning
confidence: 99%